Community-campus partnerships, collective impact, and poverty reduction. Issue 2 (14th March 2016) - Schwartz, Karen; Weaver, Liz; Pei, Natasha; Miller, Annie Kingston
Abstract: This article describes a unique Social Sciences and Humanities Research Council (SSHRC)-funded project in which a community–campus partnership is making progress in moving the needle on complex issues such as poverty. The project identified various models of community campus partnerships that help leverage collective impact efforts in poverty reduction. One model involves a center for community–university research, while others revolve around champions in the community or university who spearhead the initiatives and leverage successful partnerships into research activities. Concurrently, the campus and community partners have engaged in research with a goal of having an impact on poverty reduction. The models are examined in terms of components of collective impact: a common agenda, shared measurement, mutually reinforcing activities, continuous communication, and a backbone organization. Factors were identified that support and impede collective impact, such as the importance of a strong backbone organization, and vulnerability to personnel changes.